Efeitos da acupuntura e de mindfulness em usuárias com cefaleia primária crônica na atenção primária à saúde no município de Fortaleza-CE: estudo de viabilidade e eficácia preliminar - Girão, Athila Campos [UNIFESP] (2017)
Introduction: Mindfulness-based interventions may be effective for complementary management of primary headaches in socially vulnerable populations. This study with women from the largest favela in Ceará, Northeast Brazil, verified the effects of an IBM in women with chronic headache at social risk. Method: Preliminary, exploratory, quasi-experimental, mixed-approach (quantitative and qualitative) efficacy study evaluating the impact of an IBM on women users of SUS in relation to the disability in daily life activities (Midas) due to chronic headache (Primary outcome), as well as secondary variables such as level of mindfulness, perceived injustice and self-pity. One intervention with acupuncture was the active control group. Results: The participants' profile was: (44.5%) married; (51.3%) with up to 2 children; (63.9%) fundamental level; (53.8%) with income of 1 to 2 minimum wages and (72.21%) with chronic headache, being (63.3%) migraine and (8.8%) tension headache. Headache is associated with low schooling, low family income (p <0.05) and negative emotional events in life. In the self-reports, four social determinants of health that caused psychological distress were categorized: the social role of women in the community; Recurrent search for health services; Drug abuse and dysfunctional coping strategies. Psychological distress was at the basis of recurrent headache crises In the comparison within the IBM groups and acupuncture, IBM promoted a decrease in the level of headache inability indicated by self-reported but not by Midas; Increased self-pity (p <0.05); Increased level of mindfulness (p <0.05), whereas acupuncture promoted a decrease only in Midas (p <0.05). There was a decrease in perceived injustice in both groups, but not statistically significant (p> 0.05). In the comparison between groups, IBM presented higher levels of self-pity and mindfulness than in the acupuncture group, with a statistically significant difference (p <0.05). There were statistically significant correlations between Midas and perceived injustice (p <0.001) and Midas and mindfulness (p <0.05). In the regression model, only perceived injustice influenced Midas (p <0.001), corroborating the self-reports that highlighted this negative feeling in the genesis of headache. Final considerations and conclusions: This is the first international study to evaluate the effects of an IBM on a population of women with chronic and socially vulnerable headache compared to acupuncture. The two interventions were effective in reducing the incapacity of headache, and acting through different mechanisms. The results suggest that IBM positively influenced pain through mental and emotional processes (attention control, body awareness and emotional regulation), which did not occur in relation to the acupuncture group. The effects of IBM and acupuncture on chronic headache of the participants demonstrated preliminary potential efficacy of mind-body practices in socioeconomically vulnerable populations.